1963
DOI: 10.1677/joe.0.0270193
|View full text |Cite
|
Sign up to set email alerts
|

Response of X-Irradiated and Cryptorchid Testes to Endogenous Gonadotrophins in Parabiotic Rats

Abstract: Immature male rats were (1) exposed to X-rays, or (2) made cryptorchid, or (3) subjected to a combination of the two and placed in parabiosis with castrated males. Pairs were autopsied at various intervals up to 46 weeks and effects upon gonads and accessory sex organs evaluated.Androgen production in response to endogenous gonadotrophins from a castrated animal is greater in irradiated than cryptorchid testes. The stresses imposed upon irradiated, intra-abdominal testes greatly reduces their capacity to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Fogg and Cowing (1951) cited evidence proposed by other workers for an altered pituitary-testis axis. Some workers have shown that endogenic substances or pituitary gonadotrophins have a radioprotective action on the testis (Johnson and Witschi, 1963;Binhammer, 1967). Gunn et al (1960;, have since shown that androgen secretion by the testis is altered after radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Fogg and Cowing (1951) cited evidence proposed by other workers for an altered pituitary-testis axis. Some workers have shown that endogenic substances or pituitary gonadotrophins have a radioprotective action on the testis (Johnson and Witschi, 1963;Binhammer, 1967). Gunn et al (1960;, have since shown that androgen secretion by the testis is altered after radiation.…”
Section: Introductionmentioning
confidence: 99%